Inhibition of cholesterol biosynthesis through RNF145-dependent ubiquitination of SCAP - Li Zhang; Prashant Rajbhandari; Christina Priest; Jaspreet Sandhu; Xiaohui Wu; Ryan Temel; Antonio Castrillo; Thomas Q de Aguiar Vallim; Tamer Sallam; Peter Tontonoz (eLife, 2017)
Cholesterol homeostasis is maintained through concerted action of the SREBPs and LXRs. Here, we report that RNF145, a previously uncharacterized ER membrane ubiquitin ligase, participates in crosstalk between these critical signaling pathways. RNF145 expression is induced in response to LXR activation and high-cholesterol diet feeding. Transduction of RNF145 into mouse liver inhibits the expression of genes involved in cholesterol biosynthesis and reduces plasma cholesterol levels. Conversely, acute suppression of RNF145 via shRNA-mediated knockdown, or chronic inactivation of RNF145 by genetic deletion, potentiates the expression of cholesterol biosynthetic genes and increases cholesterol levels both in liver and plasma. Mechanistic studies show that RNF145 triggers ubiquitination of SCAP on lysine residues within a cytoplasmic loop essential for COPII binding, potentially inhibiting its transport to Golgi and subsequent processing of SREBP-2. These findings define an additional mechanism linking hepatic sterol levels to the reciprocal actions of the SREBP-2 and LXR pathways.